2021
DOI: 10.3390/genes12081131
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Fluoroquinolone-Resistant Thermophilic Campylobacter Strains Isolated from Layer Chicken Feces in Gangneung, South Korea by Whole-Genome Sequencing

Abstract: Thermophilic Campylobacter species of poultry origin have been associated with up to 80% of human campylobacteriosis cases. Layer chickens have received less attention as possible reservoirs of Campylobacter species. Initially, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of two archived Campylobacter isolates (Campylobacter jejuni strain 200605 and Campylobacter coli strain 200606) from layer chickens to five antimicrobials (ciprofloxacin, nalidixic acid, erythromyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 93 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…The rise in annually reported human infections and the evermore frequent isolation of antimicrobial-resistant C. jejuni strains from humans, animals, and the environment [ 8 , 9 ] emphasize the urgent demand for the development of “alternative-to-antibiotics” biocides [ 10 ] and for the establishment of control strategies in line with the “One Health” approach [ 11 ]. Health organizations are showing an increased interest in alternative biocides, including organic acids, phytogenics, probiotics, and prebiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The rise in annually reported human infections and the evermore frequent isolation of antimicrobial-resistant C. jejuni strains from humans, animals, and the environment [ 8 , 9 ] emphasize the urgent demand for the development of “alternative-to-antibiotics” biocides [ 10 ] and for the establishment of control strategies in line with the “One Health” approach [ 11 ]. Health organizations are showing an increased interest in alternative biocides, including organic acids, phytogenics, probiotics, and prebiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The Campylobacter genus represents a well-known group of foodborne pathogens responsible for causing self-limited gastroenteritis in humans, which sometimes requires antimicrobial treatment due to the potential for serious complications [22]. In the European Union, campylobacteriosis was the most frequently reported zoonosis in humans, It has been observed that various species within the Campylobacter genus can exchange genetic material with one another, as well as with other bacterial genera [15][16][17][18][19][20]. This facilitates the transfer of genes that enhance the virulence of Campylobacter and allow it to withstand exposure to antibiotics.…”
Section: Campylobacter Spp Overviewmentioning
confidence: 99%
“…Similarities we only identified in regard to genes cheAVW (chemotaxis), gmh, waa, kps (capsule formation), kpsDEFCST (capsular genes) and hldE (LPS-associated gene). Notably, genes expressing capsular biosynthesis were detected in C. coli strain 200606, namely Cj1416c, Cj1417c, Cj1419c and Cj1420c, suggesting potential genetic exchange between C. coli and C. jejuni species [18]. The same authors analysed the presence of virulence factors in 55 Campylobacter (C. jejuni and C. coli) isolates originating from a layer farm in South Korea.…”
Section: Virulence and Antibiotic Resistance Of Campylobacter Spp Pou...mentioning
confidence: 99%
See 1 more Smart Citation